2021
DOI: 10.21037/gs-21-603
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of ultrasound-guided erector spinae plane block on the immune function and postoperative recovery of patients undergoing radical mastectomy

Abstract: Background: To explore the effects of ultrasound-guided erector spinae plane (ESP) block on the immune function and postoperative recovery of patients undergoing radical mastectomy.Methods: One hundred and four patients with breast cancer were randomly divided into the observation group and control group, with 52 cases in each group. The control group underwent induction of routine general anesthesia and thoracic paravertebral block, while the observation group underwent ultrasoundguided ESP block combined wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
(18 reference statements)
0
4
0
Order By: Relevance
“…The inflammatory response was eliminated, signal transduction was blocked, and the noxious stimulation of peripheral nerve receptors was minimized. Furthermore, various plastic changes were suppressed in neurons, pain level was reduced, and postoperative quality-of-life was improved [29,30]. Our data showed that the probability of vomiting after surgery in the control group was higher than that in the study group; this was because the hemodynamic status of patients in the study group was relatively stable and the intake of opioid doses was reduced.…”
Section: Discussionmentioning
confidence: 68%
“…The inflammatory response was eliminated, signal transduction was blocked, and the noxious stimulation of peripheral nerve receptors was minimized. Furthermore, various plastic changes were suppressed in neurons, pain level was reduced, and postoperative quality-of-life was improved [29,30]. Our data showed that the probability of vomiting after surgery in the control group was higher than that in the study group; this was because the hemodynamic status of patients in the study group was relatively stable and the intake of opioid doses was reduced.…”
Section: Discussionmentioning
confidence: 68%
“…The implementation of an effective analgesia method can reduce the stress response to surgery in the perioperative period and is known to have a certain protective effect on the patient's immune system function. Hu et al [8], in their study comparing the effects of ESPB and Paravertebral Block (PVB) on immune functions and postoperative recovery in breast cancer patients, observed lower VAS scores and higher levels of serum CD4, CD8, and IFNɣ in the ESPB group. CD4+ T lymphocytes have a regulatory role over other lymphocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, oncological surgery, there is a positive effect on survival and metastasis, but has been ordered to regional anesthesia and analgesia techniques that have not yet been consensive [6,7]. It is thought that the sympathetic blockage formed after the erector spinae plane block (ESPB) for postoperative analgesia of breast cancer surgery suppresses the hemodynamic response of surgical stress [8].…”
mentioning
confidence: 99%
“…The application of local anesthetics keeps down the demand for volatile anesthetics and opioids while alleviating the neuroendocrine stress response and perioperative immunosuppression. The results of Hu et al found that ultrasound-guided erect spinal plane (ESP) block had little effect on immune function in patients undergoing radical mastectomy and promoted postoperative recovery (11). In recent years, intravenous lidocaine has attracted great interest from clinicians as part of the perioperative anesthetic regimen because of its analgesic, anti-hyperalgesia, and anti-inflammatory effects and its resultant shortened hospital stay.…”
Section: Introductionmentioning
confidence: 99%